Статичні характеристики синхронного двигуна з конденсаторами в колі збудження - Маляр, В.С.; Маляр, А.В.; Добушовська, І.А. (Технічна електродинаміка, 2012)
An efficient algorithm of computing static mechanical characteristics of salient-pole synchronous motors in which, in order to increase starting torque, capacitors are switched into excitation winding is proposed. The problem is solved as a boundary-value one for a system of differential equations describing asynchronous mode of operation, taking into account magnetic path saturation.